Internacionalização da pós-graduação brasileira: proposição de um framework investigativo aplicado à área de Administração Pública e de Empresas, Ciências Contábeis e Turismo - Silva, Antonia (2023)
This thesis focuses on the concept of internationalization, which refers to the form and content of the education offered by postgraduate programs. This is indicated by multilateral collaborative research (with foreign higher education institutions), dissemination of intellectual production (in international journals), mobility of faculty and students in collaboration, institutional action, and specific institutional support for internationalization (CAPES, 2019a). The overall objective of this thesis is to propose and apply a framework to investigate the internationalization process in postgraduate programs in Public Administration and Business, Accounting, and Tourism. The framework is an adaptation of the Uppsala internationalization model (JOHANSON; VAHLNE, 2009), which consists of four variables (knowledge opportunity, commitment decisions, learning acquisition through trust, and network position), using the internationalization indicators of CAPES applied in the 2017 (2013-2016) and 2021 (2017-2020) quadrennials. The methodology used is a descriptive qualitative approach, with the application of quantitative methods using the SPSS 25v.trial software. The population is comprised of forty-three postgraduate courses evaluated by the Coordination for the Improvement of Higher Education Personnel (CAPES) in the 2017 quadrennial, with a score of 5 to 7. The data was collected from the Sucupira Platform of CAPES. The data analysis included document analysis, descriptive statistics, correlation calculations, and factor analysis to adjust a model to the variables studied. As a result, a framework was developed that included two dimensions (state and flow) and four variables (knowledge of internationalization indicators, relationship indicators, internationality provided by the relationship network, and internationalization network in programs). This framework was applied to the area of Public Administration and Business, Accounting, and Tourism to investigate the internationalization process in the programs. The results showed that the researched area had internationalization initiatives driven by professional improvement and partnerships, and facilitated by international mobility, courses offered in English, publications with co-authorship from abroad, and publications in high-impact international books.Regarding the internationalization network in programs, it was possible to understand it from eight internationalization variables: faculty participation in foreign institutions, student participation in foreign institutions, participation in international research networks, international cooperation agreements and treaties, foreign faculty participation in the program, international circulation publication, student performance abroad, and strategic planning for program internationalization. In summary, this thesis proposes an investigative framework that has the potential to be replicated in other postgraduate areas, in order to highlight parameters and indicators that will signal the way forward for the program to achieve excellence in internationalization